Meta-Analysis: The Effect of HIV/AIDS in Pregnant Women Against the Incidence of Low Birth Weight and Preterm Birth - Neti Husaeni; Cusmarih Cusmarih (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Pregnancy poses a major challenge to immune system regulation. Immune function is suppressed in both HIV-infected and non-HIV-infected women. Transmission of the virus has also been reported to occur between mothers to fetuses. So that HIV infection can reduce the quality of pregnancy outcomes such as low birth weight babies (low birth weight) and premature birth (preterm) The purpose of this meta-analysis is to estimate the strength of the effect of HIV infection on the incidence of low birth weight babies and preterm delivery. This study is a systematic review and meta-analysis. Primary data is retrieved through the electronic databases PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. search keywords "HIV AND AIDS", "HIV AND pregnancy", "HIV AND pregnancy AND adjusted odds ratio", and "HIV AND Pregnancy AND adjusted odds ratio". Articles taken between 2013-2023. Statistical analysis was performed using the RevMan 5.3 application. 6 articles qualified quantitatively for analysis. women who have HIV infection during pregnancy can increase the risk of giving birth to babies with low birth weight 3.32 times and statistically significant Odds Ratio (OR 3.32; 95% CI: 2.24 – 4.93; p value < 0.001). Results also reported women who have HIV infection during pregnancy were 4.79 times more likely to giving before the due date (premature) than women who were not infected with HIV during pregnancy and had a statistically significant odds ratio (OR 4.79; 95% CI: 2.50 – 9.19; p value 0.008). HIV infection in pregnancy can increase the risk of low birth weight babies and premature birth